2020
DOI: 10.1158/1078-0432.ccr-19-3815
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Therapies Following Venetoclax Discontinuation in CLL Reveals BTK Inhibition as an Effective Strategy

Abstract: Verastem. D.M.B. serves as consultant for, is a member of the scientific advisory board of, and institution is the site of a PI clinical trial (grant paid to the institution) from AbbVie and Genentech.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 38 publications
0
113
0
2
Order By: Relevance
“…Although this observation might suggest that alloHCT can be deferred to later lines of therapy without affecting outcomes, it must be considered that successive lines of therapy are associated with lower response rates and risk of treatment related toxicities, meaning that a proportion of patients may die or become unfit before entering the next line of therapy, including alloHCT. 22,[51][52][53] Furthermore, most patients had responsive disease at the time of transplant in this cohort, thus conclusions regarding use of alloHCT in the setting of disease progression cannot be drawn from this study. With this in mind, determining the optimal timing of alloHCT needs to be carefully considered.…”
Section: Discussionmentioning
confidence: 90%
“…Although this observation might suggest that alloHCT can be deferred to later lines of therapy without affecting outcomes, it must be considered that successive lines of therapy are associated with lower response rates and risk of treatment related toxicities, meaning that a proportion of patients may die or become unfit before entering the next line of therapy, including alloHCT. 22,[51][52][53] Furthermore, most patients had responsive disease at the time of transplant in this cohort, thus conclusions regarding use of alloHCT in the setting of disease progression cannot be drawn from this study. With this in mind, determining the optimal timing of alloHCT needs to be carefully considered.…”
Section: Discussionmentioning
confidence: 90%
“…In an international, multicenter, retrospective cohort, efficacy of BTK inhibitor monotherapy does not seem to be compromised by prior venetoclax treatment. Patients achieved an 84% ORR with a median PFS of 32 months providing that they had not been previously treated with BTK inhibitors [32]. A recently published retrospective study including 23 consecutive patients with R/R CLL who received a BTK inhibitor after stopping venetoclax because of progressive disease reached similar conclusions.…”
Section: Pitfalls Of Therapy With Venetoclaxmentioning
confidence: 71%
“…While the efficacy of venetoclax after BTKi failure has been extensively reported, data for the opposite sequence are limited [30,31]. Recent results indicate that patients who discontinue venetoclax may benefit from treatment with BTK inhibitors provided that they are BTK inhibitors treatment-naïve [32,33]. In an international, multicenter, retrospective cohort, efficacy of BTK inhibitor monotherapy does not seem to be compromised by prior venetoclax treatment.…”
Section: Pitfalls Of Therapy With Venetoclaxmentioning
confidence: 98%
“…Data from clinical trials, registries, and real-world series demonstrate that most patients discontinue venetoclax because of progressive disease (PD) rather than because of adverse events. [7][8][9][10] Patients whose disease progresses on venetoclax have been shown to have traditionally high-risk features. A retrospective analysis of 445 patients treated with venetoclax on 4 early-phase clinical trials showed that patients who had received previous therapy with a Bruton tyrosine kinase inhibitor (BTKi), 3 or more previous lines of therapy, or had bulky lymphadenopathy were less likely to have a durable response to venetoclax-based therapy.…”
Section: Reasons For Progression During or After Venetoclax-based Thementioning
confidence: 99%
“…To date, the largest cohort series is a retrospective international, multicenter study that reported treatment outcomes for patients requiring treatment after venetoclax discontinuation. 10 Notably, this cohort included both patients who were BTKi naïve and those with previous exposure to BTKis. The study included 326 patients who discontinued venetoclax, 188 (58%) of whom went on to subsequent treatment.…”
Section: Covalent Btki's After Venetoclaxmentioning
confidence: 99%